PEREMPUAN DALAM KITAB SARASAMUCCAYA - Gede Mahardika (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
In the development of patriarchal culture, ideology of gender creates injustice in whichwomen are victims. The various of justifications are being made, as if the view is true andirreversible. As a result men always lead and women are led. Thus, it implies a process ofdeterioration towards women. In Sarasamuscaya, there are several verses depicting thedegradation or decline of the image of women, which puts women in a subordiated position. Theverses depicting women demeaned can be grouped into a number of categories as follows:Women as Sources of Sin and Disaster, Women as dangerous creatures and should be avoided,Women as let loose of lust, Women are difficult to understand, Women as the most sinful creature,Women as a dirty and disgusting creatures